CITRA PEREMPUAN DALAM NOVEL BUNGA-BUNGA RINDU KARYA BADRI WAHAB - Irfarettha, Santy; Abdurahman, Abdurahman; Nasution, Bakhtaruddin (Jurnal Bahasa dan Sastra, 2013)
This research means to describe the image of women in the novel of Bunga-bunga Rindu by Badri Wahab,Â  that (a) the image of women in term of phsical, (b) the image of women in trem of psychic, and (c) the image of women in trem of social development. This data of reseach is the image of women in the novel of Bunga-bunga Rindu by Badri Wahab iscreated by Libri Publizer in 2008. Based on the analysis of data are found that: (a) the image of women in trem of psycal is beutiful women, (b) the image of women in trem of psychic is diligent and smart women, (c) the image of women in trem of social can see from embrace of a women figure that: (1) as a wife, (2) as a child, (3) as a mother, (4) as a sister, (5) as a friend, (6) as a doktor, (7) as a sister in law, (8) as a house kieper, (9)as a sister in law, (10) as a teacher, (11)Â  and as a mother in law.